Analysis of Ammonia (NH₃) Levels in Dug Well Water in Apit Aiq Hamlet, Batulayar Village, Batulayar Subdistrict, West Lombok Regency - Hasanah, Uswatun; Yuliansari, Dini; Nurhidayatullah, Nurhidayatullah (Jurnal Pijar Mipa, 2025)
Dug well water is a common source of water used by rural communities. However, water pollution can pose risks to both health and the environment, such as contamination by ammonia. The sources of ammonia pollution generally originate from agricultural waste, livestock waste, and domestic household waste. The purpose of this study was to analyze the ammonia concentration and assess the feasibility of dug well water using the UV-Vis spectrophotometry method. The results of this study showed that Well 1 had an ammonia concentration of 0.045 mg/L in the first trial and 0.047 mg/L in the second trial; Well 2 had a consistent ammonia concentration of 0.224 mg/L in both trials; and Well 3 had an ammonia concentration of 0.192 mg/L in the first trial and 0.191 mg/L in the second trial. The findings indicate that Well 1 meets the Class I water quality standard of 0.01 mg/L, whereas Wells 2 and 3 do not meet this standard. However, Well 2 still meets the Class III water quality standard of 0.3 mg/L, and Well 3 meets the Class II standard of 0.2 mg/L, based on Government Regulation No. 22 of 2021. Therefore, only Well 1 is suitable for consumption, while Wells 2 and 3 are not suitable for drinking but may still be used for daily household needs. This condition is likely caused by livestock pens located approximately 11–23 meters from the wells, as well as the disposal of household and domestic waste near the dug wells, which may have seeped into the groundwater and contributed to elevated ammonia levels.